THE ROLE OF PRODUCTION FACTORS, ECONOMIC VALUE, AND THE ROLE OF THE GOVERNMENT, ON THE INTEREST OF RABBIT FARMING IN MALANG DISTRICT - Karunia Setyowati Suroto; Ariani Trisna Murti; Hidayati Karamina (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of conducting research based on a review of the formulation of the problem is to analyze and determine the factors of production, economic value, and the role of the government which have a simultaneous and partial influence on the interest in rabbit farming business in Malang Regency. This type of research uses quantitative research, namely research based on the philosophy of positivism and data collection is carried out using research instruments. The sampling method was carried out by surveying the people who had livestock and ornamental rabbits. The technique used in this study is a sampling technique with the condition that the sample used is broiler and ornamental rabbit breeders in Karangploso District, Malang Regency, which has a population of 20 rabbits and a minimum of 3 years of experience in raising livestock. The respondents were 30 farmers. Data processing is carried out through 3 stages, namely validity test, reliability test, and then multiple linear regression analysis.